2014
DOI: 10.1159/000366246
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Event Management of Oral Mucositis in Patients with Breast Cancer

Abstract: Oral mucositis (OM) is a clinically important and frequent adverse event (AE) associated with cancer treatment with conventional chemotherapy as well as new targeted agents. Incidence and severity of OM vary from treatment to treatment and from patient to patient. The pathogenesis of chemotherapy-induced OM can be divided into 5 phases. OM induced by targeted therapies differs among other things in appearance, course, concomitant AEs and toxicity, and thus could be perceived as an entity distinct from chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 36 publications
0
12
0
16
Order By: Relevance
“…At the time that the study was launched, it is conceivable that many of the participating centers would have had limited experience with mTOR inhibitor therapy. In the case of mTOR inhibitors, it has been shown that patient education, preventive measures, and early treatment with mouthwashes and/or lidocaine preparations help limit stomatitis and decrease dose interruptions [24, 25]. Potentially, the lack of familiarity of these centers with these measures may have resulted in higher toxicity and may partly explain the discrepancy in tolerability between phase I and phase II.…”
Section: Discussionmentioning
confidence: 99%
“…At the time that the study was launched, it is conceivable that many of the participating centers would have had limited experience with mTOR inhibitor therapy. In the case of mTOR inhibitors, it has been shown that patient education, preventive measures, and early treatment with mouthwashes and/or lidocaine preparations help limit stomatitis and decrease dose interruptions [24, 25]. Potentially, the lack of familiarity of these centers with these measures may have resulted in higher toxicity and may partly explain the discrepancy in tolerability between phase I and phase II.…”
Section: Discussionmentioning
confidence: 99%
“…The most common adverse events (AEs; all grades) related to 300 mg avapritinib in ≥35% of patients were nausea, fatigue, and anemia [26]. Supportive care and flexible dosing strategies (including dose interruptions and/or reductions), which are common strategies for managing AEs associated with multi-targeted TKIs [28][29][30][31][32], were used to manage the AEs seen with avapritinib in the NAVIGATOR phase I study.…”
Section: Introductionmentioning
confidence: 99%
“…This toxicity has been shown in patients receiving chemotherapy with both hematologic malignancies and solid tumours such as nonHodgkin lymphoma, breast, lung, or colorectal cancer (Rosen et al 2006;Niscola et al 2007;Blijlevens et al 2008;Seiler et al 2014). Chemotherapeutic agents such as 5-fluorouracil (5-FU), anthracyclines and taxanes are associated with a high incidence of oral mucositis (Keefe et al 2007).…”
Section: Introductionmentioning
confidence: 99%